Küreselleşme ve İktisadi Entegrasyon Bağlamında 2000 Sonrasında Türkiye Ekonomisi (Turkey in the Period of Globalization and Economic Integration: 2000 and Beyond) - Yunus Kaya (İnsan & Toplum)
This paper analyzes the process of globalization and its impact on labor, state, social inequality, and poverty in Turkey between 1980 and 2010. In 1980, Turkey had a small economy with limited industrialization, which was achieved mainly through import substitution industrialization policies. Since opening its doors to global economy, following the economic crises of the late 1970s, Turkish economy has grown rapidly, although it also suffered from frequent economic crises. In the process, Turkey has become a significant exporter of, mostly low-technology, but also increasingly medium and high technology, manufactured goods. This transformation had profound effects on the social structure of Turkey and the work life in the country. Turkey is no longer an agrarian society. In 2010, less than 25 percent of all working people were employed in agriculture compared to over 50 percent in 1980. However, after thirty years of globalization, liberalization and significant economic growth, poverty, social inequality and unemployment remain mostly unresolved. During these thirty years, Turkey experienced only modest decline in poverty while unemployment and social inequality remained high. Another significant change in Turkey during this period was the decline in the relative importance and power of the bureaucratic elite. The traditionally strong bureaucratic elite lost its direct role in the economy with the globalization of Turkish economy, which diminished its overall influence, while managerial and professional social classes expanded in size and increased their influence.